2008
DOI: 10.1007/s12079-008-0029-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CCN2 mRNA expression and promoter activity in activated hepatic stellate cells

Abstract: The matricellular protein connective tissue growth factor (CCN2) is considered a faithful marker of fibroblast activation in wound healing and in fibrosis. CCN2 is induced during activation of hepatic stellate cells (HSC). Here, we investigate the molecular basis of CCN2 gene expression in HSC. Fluoroscence activated cell sorting was used to investigate CCN2 expression in HSC in vivo in mice treated with CCl 4 . CCN2 and TGF-β mRNA expression were assessed by polymerase chain reaction as a function of culture-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…The molecular details how TGF-␤ induces CTGF production in HSCs are still largely unsolved. Current available data suggest an ALK5-dependent mechanism as dominant for this induction (26). Other signaling pathways such as the TGF-␤ non-canonical MAPK, PI3K/Akt, and PKC pathways may also participate in this process; the underlying mechanisms, however, are yet to be clarified (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular details how TGF-␤ induces CTGF production in HSCs are still largely unsolved. Current available data suggest an ALK5-dependent mechanism as dominant for this induction (26). Other signaling pathways such as the TGF-␤ non-canonical MAPK, PI3K/Akt, and PKC pathways may also participate in this process; the underlying mechanisms, however, are yet to be clarified (26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the canonical Smad pathway, TGF-␤ can also activate other signaling molecules such as Erk1/2, JNK, p38 MAPK, PKC, and PI3K/Akt, which is largely cell type-dependent (25). Previous studies have demonstrated that selective inhibition of those signaling pathways resulted in a potent reduction of CTGF mRNA expression in activated HSCs (26,27). The underlying mechanisms, however, have not been clarified yet.…”
Section: Connective Tissue Growth Factor (Ctgf)mentioning
confidence: 99%
“…We and others have shown that CCN2 mRNA and protein are expressed increasingly during progressive activation of cultured primary rat HSCs, or in response of the cells to stimulation by TGF-b, vascular endothelial growth factor, lipid peroxidation products, acetaldehyde or platelet-derived growth factor-BB [8,[13][14][15][16] . We have shown further that CCN2 promoter activity is enhanced in a Smad7-dependent fashion by TGF-b in primary rat HSCs transfected with the CCN2 promoter, luciferase reporter constr uct [10] , and that CCN2 production in the HSCs is stimulated by TGF-b1 [6] .…”
Section: Introductionmentioning
confidence: 92%
“…We have shown further that CCN2 promoter activity is enhanced in a Smad7-dependent fashion by TGF-b in primary rat HSCs transfected with the CCN2 promoter, luciferase reporter constr uct [10] , and that CCN2 production in the HSCs is stimulated by TGF-b1 [6] . We recently showed that TGF-b-induced CCN2 promoter activity in activated mouse HSCs requires Smad and Ets-1 elements in the CCN2 promoter [16] , as described for normal fibroblasts or mesangial cells [17][18][19][20] . However, CCN2 promoter activity in activated HSCs is uniquely antagonized by ALK4/5/7 inhibition [16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation